FISCAL INSTRUMENTS FOR A GREEN ECONOMY: THE ROLE OF GREEN TAXATION AND SUBSIDIES (Journal of Universal Science Research, 2025)
The shift to a green economy requires not only technological innovation but also a supportive fiscal framework. Among the most effective tools for promoting sustainable development are green taxes and environmental subsidies. These fiscal instruments serve as economic signals—penalizing environmentally harmful behavior while encouraging investment in clean technologies and renewable energy